Photoconductivities in m-plane and c-plane ZnO epitaxial films grown by chemical vapor deposition on LiGaO2 substrates: a comparative study. Issue 89 (9th September 2016) - Lin, C. H.; Chen, R. S.; Lin, Y. K.; Wang, S. B.; Chen, L. C.; Chen, K. H.; Wen, M. C.; Chou, M. M. C.; Chang, L.
Abstract : Nonpolar ( m -plane) and polar ( c -plane) ZnO epitaxial films grown by CVD exhibit superior photoconductive performance in different aspects. Abstract : The photoconduction properties of (non-polar) m -plane and (polar) c -plane ZnO thin films epitaxially grown on relatively lattice-matched LiGaO2 substrates by chemical vapor deposition have been investigated and compared. Structural and photoluminescence characterizations indicate that the c -plane ZnO films possess higher crystallinity than the m -plane ZnO films. Owing to their superior crystallinity and lower dark current, the c -plane ZnO films exhibit significantly higher optimal sensitivity ( S = 4650) to ultraviolet light than the m -plane ZnO films ( S = 10). However, in terms of photocurrent generation efficiency, the m -plane ZnO films exhibit over one order of magnitude higher responsivity ( R = 0.05–3.2 A W −1 ) than the c -plane ZnO films ( R = 0.009–0.035 A W −1 ) in the light intensity range 1.6–320 W m −2 . The probable mechanisms causing the aforementioned differences based on surface-dominant photoconduction and bulk-dominant structural and photoluminescence properties are also discussed.